Case Report: Esophago-pleural fistula found by the squamous cells from pleural effusion - Li, Shu; Han, Zesen; Zhang, Xue; Ge, Qihui; Zhao, Yingying; Lv, Shaojuan; Li, Min; Zhu, Yongchao (Frontiers in Oncology, 2025)
This report describes a case of esophago-pleural fistula (EPF) in an history of esophageal cancer (EC) patient, initially missed on CT but identified via squamous cells in pleural effusion. EPF is rare and challenging to diagnose due to subtle symptoms. The presence of squamous cells in pleural effusion, typically linked to lung cancer, initially confused the diagnosis given the patient’s EC history. Methylene blue ingestion and clinical evaluation confirmed EPF. This case emphasizes the value of pleural fluid analysis in malignancy patients and the need for vigilance in EC patients, especially with radiation-induced esophagitis.